European League Against Rheumatism recommendations for monitoring patients with systemic lupus erythematosus in clinical practice and in observational studies. Issue 7 (5th November 2009) - Mosca, M; Tani, C; Aringer, M; Bombardieri, S; Boumpas, D; Brey, R; Cervera, R; Doria, A; Jayne, D; Khamashta, M A; Kuhn, A; Gordon, C; et al.
Abstract : Objectives: To develop recommendations for monitoring patients with systemic lupus erythematosus (SLE) in clinical practice and observational studies and to develop a standardised core set of variables to monitor SLE. Methods: We followed the European League Against Rheumatism (EULAR) standardised procedures for guideline development. The following techniques were applied: nominal groups, Delphi surveys for prioritisation, small group discussion, systematic literature review and two Delphi rounds to obtain agreement. The panel included rheumatologists, internists, dermatologists, a nephrologist and an expert related to national research agencies. The level of evidence and grading of recommendations were determined according to the Levels of Evidence and Grades of Recommendations of the Oxford Centre for Evidence-Based Medicine. Results: A total of 10 recommendations have been developed, covering the following aspects: patient assessment, cardiovascular risk factors, other risk factors (osteoporosis, cancer), infection risk (screening, vaccination, monitoring), frequency of assessments, laboratory tests, mucocutaneous involvement, kidney monitoring, neuropsychological manifestations and ophthalmology assessment. A 'core set' of minimal variables for the assessment and monitoring of patients with SLE in clinical practice was developed that included some of the recommendations. In addition to the recommendations, indications for specific organ assessments that were viewed as part of good clinical practice were discussed and included in the flow chart. Conclusions: A set of recommendations for monitoring patients with SLE in routine clinical practice has been developed. The use of a standardised core set to monitor patients with SLE should facilitate clinical practice, as well as the quality control of care for patients with SLE, and the collection and comparison of data in observational studies.